A influência do Zen budismo nas artes marciais japonesas no Brasil - Farias, André Alves (2009)
This research aimed to contextualize the transformations observed through specific eras of the Japanese history about religious and martial contents of the Japanese martial in Brazil. Japanese martial arts is called Budo (The way of War) and the specific one chosen for this research is called Kendo (the way of Sword). The main difference regarding this kind of martial arts compared to others existing in Brazil is the coexistence of historical, ethnic and religious contents that, apparently, are bringing to the Brazilian culture ethical and moral assumptions from Buda s teachings. Through interviews we focused on the investigation about nonphysical manifestation which exists in Kendo. There were two groups, organized according to their official scale. The information led us to conclude that the philosophical, ethical and religious understanding about Kendo is gaining more and more local characteristics